Combined Operation of SVC, PSS and Increasing Inertia of Machine for Power System Transient Stability Enhancement - Bablesh Kumar Jha; Ramjee Prasad Gupta; Upendra Prasad (International Journal of Applied Power Engineering (IJAPE), 2014)
In this paper improvement of transient stability by coordination of PSS (Power System Stabilizer) and SVC (Static var Compensator) and increasing inertia of synchronous machine has been observed. Because single method is not sufficient for improving stability. For this purpose a 9 bus multi machine system has been considered. Transient stability improvement has been tested subjected to three phase fault at bus 3 after 0.5 second and fault has been cleared after 1 second. By the use of PSS, SVC and by increasing inertia method for the test system the electromechanical oscillation for generator electrical power has been reduced and the steady state power transfer has been enhanced. In this paper the Inertia of the machine is not so much increased. Because after increasing inertia of the machine rotor will be havier.so that it is kept always within limit as considering its reliability and economy. And field voltage is also kept limited